FAST FREQUENCY RESPONSE CALCULATIONS OF CAVITY-BACKED APERTURE ANTENNAS USING HYBRID FEM/MOM TECHNIQUE IN CONJUNCTION WITH MODEL BASED PARAMETER ESTIMATION - Reddy, C. J. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Model Based Parameter Estimation (MBPE) is presented in conjunction with the hybrid Finite Element Method (FEM)/Method of Moments (MoM) technique for fast computation of the input characteristics of cavity-backed aperture antennas over a frequency range. The hybrid FEM/MoM technique is used to form an integro-partial-differential equation to compute the electric field distribution of a cavity-backed aperture antenna. In MBPE, the electric field is expanded as a rational function of two polynomials. The coefficients of the rational function are obtained using the frequency derivatives of the integro-partial-differential equation formed by the hybrid FEM/MoM technique. Using the rational function approximation, the electric field is calculated and the input characteristics of the antenna are obtained over the frequency range. Numerical results for an open coaxial line and a cavity-backed microstrip patch antenna are presented. Good agreement between MBPE and the solutions over individual frequencies is observed. CPU timings for all numerical calculations are presented.